Transforming the invisible into the visible: disparities in the access to health in LGBT+ older people (Clinics, 2022)
Objectives: To compare variables of access to healthcare between the LGBT+ population aged 50 and over and those non-LGBT+.Methods: A cross-sectional study was carried out in Brazil through a confidential online questionnaire. The use of the health system was characterized by the number of preventive tests performed and measured by the PCATool-Brasil scale (a 10-point scale in which higher scores were associated with better assistance in healthcare). The association between being LGBT+ and access to health was analyzed in Poisson regression models.Results: 6693 participants (1332 LGBT+ and 5361 non-LGBT+) with a median age of 60 years were included. In the univariate analysis, it was observed not only lower scores on the PCATool scale (5.13 against 5.82, p < 0.001), but a greater proportion of individuals among those classified with the worst quintile of access to healthcare (< 4 points), 31% against 18% (p < 0.001). Being LGBT+ was an independent factor associated with worse access to health (PR = 2.5, 95% CI 2.04‒3.06). The rate of screening cancer, for breast, colon, and cervical cancer was also found to be lower in the LGBT+ population.Conclusion: Healthcare access and health service experiences were worse in the LGBT+ group than in their non-LGBT peers. Inclusive and effective healthcare public policies are essential to promote healthy aging for all.